If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+(6x-4)=11
We simplify the equation to the form, which is simple to understand
3+(6x-4)=11
Remove unnecessary parentheses
+3+6x-4=+11
We move all terms containing x to the left and all other terms to the right.
+6x=+11-3+4
We simplify left and right side of the equation.
+6x=+12
We divide both sides of the equation by 6 to get x.
x=2
| 6+1/5x-1/3x=268/45 | | -9/35=-4/7x-x+1 | | 1/9+6x+2x=145/9 | | 7x+7/9-1/5x=2081/315 | | 4x+3+3x=23/3 | | -7+2/3x+2x=-25/3 | | -1002/7=6x+6x+6/7 | | (x-3)(x^2-2x+6)=x(x^2-5x+9) | | -3/7x+7+1/2x=93/14 | | 5x-5/9+1/2x=287/18 | | -6/7+2x+7x=57/7 | | -59/7=3x-5/7x-9 | | 3x+1-6x=-35 | | 6x-3+2/7x=73/49 | | -2/3-5x+3/7x=-26/7 | | 5/18=3x-4x+7/9 | | 6+x+4/5x=69/10 | | -6x+1/3-6/7x=481/147 | | 3/5+1/3x+5x=3/5 | | 8-6/7x+7x=51 | | 1+5/7x+2x=197/7 | | x+1/2+x=5/2 | | 7x*14=0 | | 3a+4=25 | | -137/28=2x+7x+1/4 | | 3/7+2x+2/5x=-6/35 | | 6/7x+3/5+2x=-579/35 | | x-3+1/2x=9/2 | | 5-7x-5x=-67 | | -19/120=-1/3x-x+3/8 | | 5x-5+1/3x=-23/3 | | x+9+5/7x=-33/7 |